Vinko Jelić and Ivan Lukačić: Two Migrants Between the Mediterranean and Central Europe in the MusMig Project and Its Database - Katalinić, Vjera (De musica disserenda, 2017)
The author presents phases in the work on the database within the European HERA project Music Migrations in the Early Modern Age: the Meeting of the European East, West and South (2013–2016), illustrated by two case studies from the Croatian lands. Vinko Jelić from Rijeka and Ivan Lukačić from Šibenik were contemporaries of the Parnassus Musicus Ferdinandaeus generation but their output was not included in the anthology. The data on their life, education and work was entered in the database, as well as data on 3500 other European musicians investigated in the MusMig project. On the basis of the search results, their timelines and possible encounters with other musicians are outlined.